Synergistic enhancement effect of SiC whisker and nano-particle on mechanical properties of Co4Sb11.5Te0.5 skutterudite. (August 2020) - Guo, Feng; Wen, Pengfei; Duan, Bo; Li, Yao; Zhou, Xilong; Zhai, Pengcheng
Abstract: Co4 Sb11.5 Te0.5 hybrid composites with dual-nano inclusions (1 vol %) of SiC whiskers (SiCw ) and SiC particles (SiCp ) are prepared by spark plasma sintering. It is found that the hybrid composites exhibit further improved flexural strength and fracture toughness compared with those reinforced by SiCw or SiCp alone, indicating a striking synergistic enhancement effect. And the dimensionless figure of merit values of the hybrid composites remain nearly unchanged compared with the sample reinforced by individual inclusion. Our study provides an effective route to further improve the mechanical prosperities of thermoelectric materials. Graphical abstract: Image, graphical abstract